Pembelajaran Daring di Sekolah Dasar Kecamatan Kradenan Kabupaten Blora - Rista Utami, Novia Rahma (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This cross-site qualitative research describes the online learning prosess and the impact of covid-19 on learning. The research subjects are teachers and high school students using interviews, observations, and documentation. The online learning process is planned by selecting meterials, carried out using an android and whatsapp, starting at 07.00 WIB with assiggment. No process assessment. The interaction between teachers and students is one-way, not learning through activities. The obstacles are minimal internet, passive students, not enthusiastic, and lack of parental support. Positive impact, teachers know parental support for children’s education, teachers conduct IT-based learning, and flexible study time. The negative impact is that students do not understand the material.